2015
DOI: 10.1111/xen.12157
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation from the perspective of moral theology

Abstract: Background: Current medical research in the area of xenotransplantation is driven by the aim to save human lives and to improve the quality of life of those suffering from organ insufficiencies. Methods: This study reflects the therapeutic intent of xenotransplantation from a theological-ethical perspective. Regarding statements of Christian communities, the analysis focuses mainly on catholic documents. This study takes into account the document on Prospects for Xenotransplantation by the Pontifical Academy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Although not a topic of this review, it should be mentioned that theological-ethical [105][106][107] and regulatory aspects of xenotransplantation are being broadly discussed. The International Xenotransplantation Association [IXA] recently published the first update of a consensus paper dealing with different aspects of efficient and safe islet cell xenotransplantation [108][109][110][111][112][113][114][115].…”
Section: Ethical Aspects and Regulationmentioning
confidence: 99%
“…Although not a topic of this review, it should be mentioned that theological-ethical [105][106][107] and regulatory aspects of xenotransplantation are being broadly discussed. The International Xenotransplantation Association [IXA] recently published the first update of a consensus paper dealing with different aspects of efficient and safe islet cell xenotransplantation [108][109][110][111][112][113][114][115].…”
Section: Ethical Aspects and Regulationmentioning
confidence: 99%
“…Moral and ethical questions are important foundational concerns in xenotransplantation that have received significant attention. [2][3][4][5][6] However, future clinical trials need more discussion and exploration with regard to the practical psychosocial factors that may be of clinical importance to the transplant team. A search of the literature found <200 articles published between 2000 and 2015 that related to psychosocial components of xenotransplantation.…”
Section: Psychosocial Challenges Of Xenotransplantation: the Need Formentioning
confidence: 99%
“…2,7,8,[11][12][13][14][15][16][17]24,25 A tentative profile has been built up about those groups who are more likely to support the procedure. 2,7,[12][13][14]17,24 Some reports found that the general public was more disposed toward this form of therapy than were hospital personnel, 8,14,15 an observation that is perhaps confusing and potentially problematic. There remains, however, a lack of information on the relationship between a patient's theological beliefs (including atheists) and his or her personal attitude toward xenotransplantation, particularly in regard to those who may be opposed to xenotransplantation.…”
Section: Psychosocial Challenges Of Xenotransplantation: the Need Formentioning
confidence: 99%
“…They can affect one's own identity and self‐image and thus also affect religious dimensions. Hence, they make a comprehensive range of accompaniment necessary …”
Section: Introductionmentioning
confidence: 99%